Chemical Safety Awareness Among Staff And Students In Secondary Schools In The State Of Penang - Nesan, Kartikeyan Patma (2018)
A study on chemical safety awareness among staff and students in secondary schools in Penang was conducted. Survey forms were given to staff and students in 20 chosen schools in all districts of Penang. The forms were collected safely. The surveys were done to determine the level of awareness and the elements that have the higher and lower awareness among staff and students. The awareness was tested using elements that involve laboratory management and chemical management, Personal Protective Equipments(PPE), safe procedure and practices, operational control methods, training and education, emergency and first aid, Chemical Safety Data Sheet, warning signs and recordkeeping.